Unlocking career choices: The role of Self-Efficacy Final-Year Students Decision Making - Hermawan, Michael Geri; Novita, Maria Prima (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Final year students are often associated with problems in career decision making, one of these factors is student beliefs, in this case self-efficacy. This research aims to determine the relationship between self-efficacy and career decision making. The research was conducted using quantitative correlational methods, subjects were recruited using accidental sampling techniques and found 300 final year students in Central Java with 61% female subjects and 39% male subjects. The measuring instruments used are the General Self Efficacy Scale (GSES) and the Career Decision Making Proficiency Scale (CDMPS). Based on data that has been processed using the Spearman rho correlation test, it is stated that there is a significant positive relationship between self-efficacy and career decision making in final year students in Central Java with a value of r = 0.172 and sig. = 0.001, which indicates that the higher the self-efficacy, the higher the career decision making. This emphasizes the importance of the relationship between self-efficacy and career decision making, by motivating students and convincing students in their career choices, which increases confidence in the career choices they choose.Mahasiswa tingkat akhir seringkali dikaitkan dengan permasalahan dalam pengambilan keputusan karier salah satu faktor tersebut adalah keyakinan mahasiswa dalam hal ini efikasi diri. Penelitian ini bertujuan untuk mengetahui hubungan antara efikasi diri dengan career decision making. Penelitian dilakukan menggunakan metode kuantitatif korelasional,subjek direkrut menggunakan teknik accidental sampling dan ditemukan 300 mahasiswa tingkat akhir di Jawa Tengahdengan subjek perempuan sebanyak 61% dan laki-laki 39%. Alat ukur yang digunakan adalah skala General Self Efficacy Scale (GSES) dan Career Decision Making Proficiency Scale (CDMPS). Berdasarkan data yang telah diolah menggunakan uji korelasi spearman rho, dinyatakan ada hubungan positif dan signifikan (r = 0,172, sig.= 0,001) antara efikasi diri dengan career decision making pada mahasiswa tahun terahir di Jawa Tengah, yang mengindikasikan bahwa semakin tinggi efikasi diri, semakin tinggi career decision making. Hal tersebut menekankan kepentingan hubungan antara efikasi diri dengan career decision making, dengan memotivasi mahasiswa dan meyakinkan mahasiswa dalam pilihan karier mereka, yang meningkatkan keyakinan dari pilihan karier yang mereka pilih.